(untitled) (The International Journal of Educational Sciences and Arts, 2025)
This study aims to investigate the ability of Saudi EFL learners to recognize the syllable number in various types of words. The study sample consisted of Saudi male and female students at Al-Baha University majoring in English Language. These students had completed many of the program courses; among which were the courses of ‘Phonetics’ and ‘Phonology’. The researcher adopted the descriptive analytic method to conduct the study. To collect the data, a test was constructed containing various types of words and sent to the participants using a link of Google forms. 30 respondents sent back their responses which composed the data to be analyzed. The researcher used the program of Google Forms to come out with Pie Charts displaying the performance of the participants. The data were analyzed to answer the study questions. The findings revealed that Saudi EFL learners showed acceptable performance in recognizing the syllable number in English words. It is also noticeable that longer words with four syllables or more might be more difficult to account for than shorter ones.